Propaganda Pemberitaan Jokowi pada Pemilu 2014 di Majalah Tempo dalam Perspektif Ideologies And Power - Marini Marini; Nurlaillah Sari Amallah; Andi M. Faisal Bakti; Makroen Sanjaya (Dakwah Institut PTIQ Jakarta, 2023)
Tempo magazine is one of the media that is in the line of 'loving' Jokowi. Tempo Magazine doubled Jokowi in the 2014 election as a modest man and a hobby of blusukan. This is based on the total duration, frequency, and tendency of the object of the news to Jokowi. Jokowi's image, which was initially positive, especially during the 2014 presidential election campaign, immediately changed after Jokowi became president in the news of Tempo Magazine. This was proven by Tempo Magazine supporting Jokowi during the 2014 presidential election because it was based on his ideology that Prabowo Subianto was a human rights criminal. In the 5-11 August 2013 edition of Tempo Magazine, they gave the title “Suddenly Jokowi” with a picture of Jokowi singing in pause. This tendency is a form of the failure of Tempo Magazine to become a balanced media. Tempo magazine chose issues, used angles, and published 11 out of 20 total Main Reports using the glittering generalities propaganda technique. The theory used is from Branston and Stafford (2003: 117-133) namely marxist approaches, post-marxism and critical pluralism, and discourses and lived culture. The relevant concepts are mukhtalif, kabilah, dan al-hadarah. Tempo Magazine's reporting sparked polarization, as seen from the concentration in political currents and ideology. The existence of this news as a political message that is more effective in raising issues to the public.